Analysis of the Mixture Fuels to the Performance of Diesel Engine - Winoko, Yuniarto Agus; Arifin, Indra Nurzainu; Ro'isatin, Umi Anis (University of Muhammadiyah Malang, 2019)
The demand for fuel is increasing every year that the supply comes to decrease. Biodiesel is an alternative energy for diesel fuel. It has the same characteristics as diesel fuel. It also renewable and environmentally friendly. The mixture of biodiesel and diesel fuel lessens the concentration of hydrocarbons and increases the cetane value. Therefore, combustion occurs completely. The purpose of this research is to compare the power, SFC and exhaust emission of direct injection engines with B-20 fuel to those with diesel fuel. The method to test the engine power uses ISO 1585 where the engine speed range starts from 1000-4000 rpm. The test results show that the engine has better performance when it uses mixture fuels but it is not for the engine with diesel fuel. The mixture fuels give higher power to the engine, but less emission. It is the opposite of the engine with diesel fuel, even though the difference in power is slight. It can be concluded that the mixture fuels influence the performance of direct injection engine.